THE ROLE OF CRM SYSTEMS IN THE USE OF DIGITAL MARKETING STRATEGIES IN COMMERCIAL BANKS (Marketing Journal, 2025)
This study analyzes the critical role of Customer Relationship Management (CRM) systems in implementing digital marketing strategies in commercial banks . The importance of CRM systems in improving banking service efficiency , strengthening customer loyalty , and ensuring competitiveness is examined . Methodologically , the study applies secondary data analysis and a systematic review of industry reports . Practical recommendations are proposed for the implementation of CRM systems in Uzbekistanʼs banking sector .
Keywords: CRM systems; digital marketing; commercial banks; customer loyalty; digital transformation; banking services